The Psychological Effects of Environmental Degradation on Human Well-Being - Makeda, Kelly (International Journal of Humanity and Social Sciences, 2024)
Purpose: This study sought to investigate the psychological effects of environmental degradation on human well- being. Methodology: The study adopted a desktop research methodology. Desk research refers to secondary data or that which can be collected without fieldwork. Desk research is basically involved in collecting data from existing resources hence it is often considered a low cost technique as compared to field research, as the main cost is involved in executive's time, telephone charges and directories. Thus, the study relied on already published studies, reports and statistics. This secondary data was easily accessed through the online journals and library. Findings: The findings reveal that there exists a contextual and methodological gap relating to the psychological effects of environmental degradation on human well- being. Through a comprehensive review of empirical studies, it revealed the pervasive nature of environmental degradation's impact on human mental health, consistently finding associations between exposure to various environmental stressors and adverse psychological outcomes. The study emphasized the interconnectedness between environmental health and human well-being, highlighting the need for holistic approaches to sustainability that integrate mental health considerations. It underscored the importance of community engagement and participatory approaches in addressing the psychological effects of environmental degradation, advocating for community-based interventions to promote resilience and sustainable development. Unique Contribution to Theory, Practice and Policy: The Ecopsychology theory, Conservation Psychology theory and Stress and Coping theory may be used to anchor future studies on the psychological effects of environmental degradation on human well- being. The study offered valuable recommendations that contributed to theory, practice, and policy. It emphasized the need for an integrated theoretical framework that accounted for the multidimensional nature of environmental degradation and its psychological impacts. The recommendations highlighted the importance of integrating mental health considerations into environmental conservation efforts, promoting nature-based interventions, and prioritizing evidence-based policy reforms. Community engagement, interdisciplinary collaboration, and longitudinal research were identified as key strategies for addressing the psychological effects of environmental degradation and fostering resilience. Overall, the study provided a comprehensive roadmap for advancing understanding and addressing the complex interplay between environmental change and mental health outcomes.